MENGUNGKAPKAN SISI POSITIF SOCIAL MEDIA USE: PERANNYA TERHADAP DIGITAL WELL-BEING PADA MAHASISWA - Felicya Cardella; Zamralita; Fahlevi, Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social media has become an integrated part of university students' daily lives, influencing their mental and emotional well-being as well as their academic activities. On one hand, social media use facilitates communication, expands social networks, and supports learning activities. On the other hand, it could also lead to negative outcomes such as distraction, decreased academic performance, and increased social pressure. Therefore, it is important to understand the role of Social Media Use in university student’s Digital Well-Being. This study employed a quantitative correlational design using a convenience sampling technique involving 488 university students who uses social media. Social Media Use was measured using the Social Media Use Integration Scale (SMUIS) developed by Jenkins-Guarnieri et al. (2013), while Digital Well-Being was measured using the Digital Well-Being Scale developed by Mathew et al. (2023). The results revealed that Social Media Use plays a significantly positive role in student’s Digital Well-Being (R = 0.437, p < .001). Regression analysis showed a coefficient of determination of R² = 0.191, indicating that Social Media Use accounts for 19.1% of the variance in student's Digital Well-Being. These findings suggest that higher levels of Social Media Use are associated with higher levels of Digital Well-Being among university students.